Upaya Penanggulangan Tindak Pidana Penyalahgunaan Narkotika Oleh Anak - Putri Mauliza Fonna; Ediwarman Ediwarman; Mahmud Mulyadi (Mahesa Research Center, 2023)
The purpose of this study is to analyze the rule of law in dealing with criminal acts of narcotics abuse by children in the Legal Area of the North Sumatra Regional Police and the obstacles they face. The type used in this research is normative juridical and analytical descriptive in nature. The results of the study state that the regulation of narcotics abuse is regulated in Article 127 paragraphs (1), (2) and (3) of the Narcotics Law, punishable by imprisonment under 7 (seven) years. The provisions of Article 111, whoever owns it, carries a penalty of imprisonment for more than 7 (seven) years based on the modus operandi of child abuse, so that diversion cannot be attempted at the three levels based on the provisions of the Juvenile Criminal Justice System Act. The handling of criminal acts of narcotics abuse by children in the Legal Area of the Regional Police of Sumatra is carried out through means of criminal law (Repressive) and non-criminal law means (Preventive). Internal obstacles faced in overcoming criminal acts of narcotics abuse by children in the jurisdiction of the Sumatra Regional Police, include: Budget, office facilities, operational facilities, operational facilities, while external factors such as lack of community participation and drug dealers usually have high mobility.